(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Employee engagement has emerged as a popular organizational concept in recent years. It is the level of commitment and involvement an employee has towards their organization and its values and beliefs. An engaged employee is aware of business context, and works with colleagues to improve performance within the job for the benefit of the organization culture. Employee engagement initiative has a direct impact on the organization’s productivity. All organizations want their employees to be engaged in their work. Employee engagement is linked to customer satisfaction which is linked to an organization’s financial success. Engagement comes about when enough people care about doing a good job and care about what the organization is trying to achieve and how it goes about doing it. This caring attitude and behavior only comes about when people get satisfaction from the jobs they do believe that the organization supports them and work with an effective HR manager. In this paper a literature review from various research findings and corporate practices are employed using a descriptive study technique. It projects the impact of employee engagement on organization’s productivity. It also presents the factors influencing the employee engagement and organizational outcomes.